2003
DOI: 10.1128/aac.47.7.2249-2255.2003
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Transitional Zones, Areas whereHelicobacterTreatment Fails: Results of a Treatment Trial Using the Sydney Strain Mouse Model

Abstract: Current combination therapies cure Helicobacter pylori infection in 75 to 85% of cases. However, many treatment failures are not explained by antibiotic resistance. Our goal was to explore treatment failures under in vivo conditions by using the H. pylori Sydney strain (SS1) mouse model. Mice infected with H. pylori (SS1) were treated with monotherapies or combination therapies used in human trials. Bacterial levels and distribution of organisms within the stomach were assessed 24 h after treatment to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
0
26
1
1
Order By: Relevance
“…Thus, drugs that concentrate in areas of inflammation (serum leakage) are likely to be the most effective against H. pylori, such as MTZ, which also tends to concentrate in gastric acid (41). Our group and others have shown that MTZ is the most effective monotherapy for the treatment of mice colonized by strains of H. pylori that are susceptible to MTZ (42,43). The remarkable efficacy of amixicile as a monotherapy was unexpected, since neither amoxicillin nor clarithromycin, a mainline therapeutic used for the treatment of H. pylori in humans, shows any efficacy as a monotherapy in this model (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, drugs that concentrate in areas of inflammation (serum leakage) are likely to be the most effective against H. pylori, such as MTZ, which also tends to concentrate in gastric acid (41). Our group and others have shown that MTZ is the most effective monotherapy for the treatment of mice colonized by strains of H. pylori that are susceptible to MTZ (42,43). The remarkable efficacy of amixicile as a monotherapy was unexpected, since neither amoxicillin nor clarithromycin, a mainline therapeutic used for the treatment of H. pylori in humans, shows any efficacy as a monotherapy in this model (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have shown that MTZ is the most effective monotherapy for the treatment of mice colonized by strains of H. pylori that are susceptible to MTZ (42,43). The remarkable efficacy of amixicile as a monotherapy was unexpected, since neither amoxicillin nor clarithromycin, a mainline therapeutic used for the treatment of H. pylori in humans, shows any efficacy as a monotherapy in this model (42,43). On the basis of these results, we suggest that amixicile most likely concentrates in areas of inflammation associated with active infections.…”
Section: Discussionmentioning
confidence: 99%
“…The test sample (50 mg/kg/day) and the antibiotics were suspended in 0.5% hydroxypropylmethylcellulose. Each animal received the corresponding treatment twice daily for 7 days (46). Animals were sacrificed 36 h and 29 days, respectively, after the cessation of treatment for the assessment of H. pylori colonization for clearance and eradication profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the antibiotics used to eliminate H pylori must achieve inhibitory or bactericidal concentrations at the site of infection. The antibiotics are usually taken orally, and thus the thickness of the mucus layer, the shape and motility of the stomach, and the acidic environment may all contribute to inadequate distribution and concentration of the drugs at the surface of the gastric mucosa [6] . When treating H pylori infections by oral administration, some areas of the stomach, such as the crypts and folds of the gastric body or the transitional zones between the different gastric zones, are not sufficiently exposed to locally acting drugs [7] .…”
Section: Introductionmentioning
confidence: 99%